The effects of small-scale impoundments and bank reinforcing on fish habitat and composition in semi-natural streams - Monaghan, Kieran A. (2008)
We studied the fish assemblages of thirty one, 2(nd)-4(th) order "least- impacted" streams with a varying degree of low-level management in central Portugal, using a standardised survey to document the river habitat. Channel, banks and riparian landuse, described separately according to principal component scores, were significantly related to altitude, slope and management intervention. Species diversity was low, represented by four endemic, four pan-European and one exotic species. TWINSPAN classification distinguished 3 community types, characterised by their dominant species: trout (Salmo trutta L.), chub (Leuciscus carolitertii Doadrio) and "roach" (Squalius alburnoides Steindachner and Chondrostoma oligolepis Robalo). Community types were associated with environmental differences with PC Channel scores higher at trout sites compared to other classification groups, whilst PC Bank-1 scores, temperature and conductivity were significantly different at trout compared to "roach" sites. Ecologically important habitat features were, in turn, related to landscape (map-derived) parameters and the extent of channel and bank management. The mis-classification of sites in discriminant analysis was related to management intervention, indicating the potential difficulty in the assignment river-community types for the biological monitoring of fish communities in these stream types.